Aerodynamic Optimization Design of a Multistage Centrifugal Steam Turbine and Its Off-Design Performance Analysis - Hui Li; Dian-Gui Huang (International Journal of Rotating Machinery)
Centrifugal turbine which has less land occupation, simple structure, and high aerodynamic efficiency is suitable to be used as small to medium size steam turbines or waste heat recovery plant. In this paper, one-dimensional design of a multistage centrifugal steam turbine was performed by using in-house one-dimensional aerodynamic design program. In addition, three-dimensional numerical simulation was also performed in order to analyze design and off-design aerodynamic performance of the proposed centrifugal steam turbine. The results exhibit reasonable flow field and smooth streamline; the aerodynamic performance of the designed turbine meets our initial expectations. These results indicate that the one-dimensional aerodynamic design program is reliable and effective. The off-design aerodynamic performance of centrifugal steam turbine was analyzed, and the results show that the mass flow increases with the decrease of the pressure ratio at a constant speed, until the critical mass flow is reached. The efficiency curve with the pressure ratio has an optimum efficiency point. And the pressure ratio of the optimum efficiency agrees well with that of the one-dimensional design. The shaft power decreases as the pressure ratio increases at a constant speed. Overall, the centrifugal turbine has a wide range and good off-design aerodynamic performance.